2005 IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR'05)
DOI: 10.1109/cvpr.2005.240
|View full text |Cite
|
Sign up to set email alerts
|

Multilinear Independent Components Analysis

Abstract: Independent Components Analysis (ICA) maximizes the statistical independence of the representational components of a training image ensemble, but it cannot distinguish between the different factors, or modes, inherent to image formation, including scene structure, illumination, and imaging. We introduce a nonlinear, multifactor model that generalizes ICA. Our Multilinear ICA (MICA) model of image ensembles learns the statistically independent components of multiple factors. Whereas ICA employs linear (matrix) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
1

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 10 publications
0
88
0
1
Order By: Relevance
“…Thus, for analysis and processing, more appropriate are methods that directly account for data dimensionality. In this respect, it was shown that tensor-based methods frequently offer many benefits, such as in the case of the tensorfaces, as well as view synthesis proposed by Vasilescu and Terzopoulos [48][49][50], or data dimensionality reduction by Wang and Ahuja [51,52], handwritten digits recognition proposed by Savas and Eldén [42] or road signs recognition by Cyganek [9], to name a few. In this section, we present a brief introduction to the tensor analysis necessary for understanding of further parts of this paper.…”
Section: Signal Processing With Tensorsmentioning
confidence: 99%
“…Thus, for analysis and processing, more appropriate are methods that directly account for data dimensionality. In this respect, it was shown that tensor-based methods frequently offer many benefits, such as in the case of the tensorfaces, as well as view synthesis proposed by Vasilescu and Terzopoulos [48][49][50], or data dimensionality reduction by Wang and Ahuja [51,52], handwritten digits recognition proposed by Savas and Eldén [42] or road signs recognition by Cyganek [9], to name a few. In this section, we present a brief introduction to the tensor analysis necessary for understanding of further parts of this paper.…”
Section: Signal Processing With Tensorsmentioning
confidence: 99%
“…Multilinear analysis was introduced to the computer vision community by Vasilescou and Terzopoulos [1][2][3][4]. Multilinear data represent the natural extension from scalars (0-D tensors), through vectors (1D tensor) and matrices (2D tensors) to general ndimensional data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [3] Vasilescou et al approximated the solution using a two step minimisation i.e. first they find the best linear parameters, rij...k that minimise:…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been applied successfully in face recognition [24], psychometric [19], and image analysis [25]. Two popular models have been studied for tensor factorization including the parafac model [8,3] and the tucker model [23].…”
Section: Related Workmentioning
confidence: 99%
“…They have been commonly applied for the analysis of such data for data compression, visualization, and detection of hidden information (factors), e.g., in face recognition [24], psychometric [19] and image analysis [25]. Additionally, the basis can be constrained to be sparse which typically leads to an even more meaningful decomposition of the data.…”
Section: Introductionmentioning
confidence: 99%